Anteseden Perilaku Manajemen Keuangan pada Generasi Z - Utami, Budi Barata Kusuma; Fikri, Muhammad Ali (Jurnal Manajemen Bisnis dan Keuangan, 2024)
A good financial attitude and financial knowledge can improve financial management behavior. Role locus of control can also be a supporting factor in financial attitudes and knowledge in improving financial management behavior. The aim of this research is to analyze the effect of financial attitudes and financial knowledge on financial management behavior through locus of control. This research was conducted on 90 generation Z in Yogyakarta. This research succeeded in proving; 1) financial attitudes affects financial management behavior; 2) financial attitudes affects locus of control; 3) financial knowledge affects financial management behavior; 4) financial attitudes affects locus of control; 5) locus of control affects financial management behavior; 6) locus of control mediation on financial attitudes towards financial management behavior; and 7) locus of control mediation on financial knowledge on financial management behavior.